The Effect of Implementing Musi Board Media (Multi Function) on Student Learning Outcomes in Class IV FPB Material at Cot Angan Elementary School, Aceh Besar Regency - Muzkiati, Muzkiati; Ahadin, Ahadin; vitoria, linda (Elementary Education Research, 2024)
This study aims: 1) To find out the learning activities of students in participating in learning using musi board media in class IV FPB material at SDN Cot Angan Aceh Besar District 2) To determine the effect of applying musi board media to student learning outcomes in class IV FPB material in SDN Cot Angan, Aceh Besar District. The design in this research is classroom action research with an experimental approach consisting of 2 cycles, and each cycle includes 4 stages: planning, action, observation, and reflection. The population in this study were 20 grade IV students of Cot Angan Public Elementary School, Aceh Besar District. Data collection techniques using observation sheets and tests. Based on the results of data analysis, it can be concluded that the average activity of students during the learning process by applying the musi board media in the first cycle was 2.85 and in the second cycle it increased to 3.57. Student learning outcomes show a significance value (2-tailed) on the test, namely 0.000 0.05, where the average student learning outcomes in cycle I is 62.25 and in cycle II the average learning outcomes experience an increase of 83, 00. The average value of learning outcomes obtained by these students can meet the KKM. So it can be said that there is an influence of multi-function board media (musi) on student learning outcomes in FPB material.